A study of consumer-generated advertising—An experimental analysis based on purchase experiences, information channels, and privacy costs - Chuanxi Cai; Yu Liu (PLoS ONE, 2026)
Taking consumer-generated advertising as the research object, hypotheses are proposed on the influential relationship between purchase experiences, information channels and privacy costs and consumer-generated advertising. Then, a between-groups experimental design was adopted. For 402 samples, through questionnaires and interview experiments, ANOVA was used to analyze consumer-generated advertising, exploring the relationship between the behavior of consumer-generated advertising and their influence factors in different consumption scenarios. The results of the study show that: (1)information channels, purchase experiences and privacy costs all have significant effects on consumer-generated advertising. (2)The effect of purchase experiences on consumer-generated advertising is moderated by information channels. (3)The effect of privacy costs on consumer-generated advertising is moderated by information channels and purchase experiences. (4)There is no significant interaction effect among purchase experiences, information channels and privacy costs. The results of the study are helpful for enterprises to manage consumer-generated advertising reasonably and enhance the marketing management capabilities of enterprises.